Degassing at the Volcanic/Geothermal System of Kos (Greece): Geochemical Characterization of the Released Gases and CO2 Output Estimation. (26th June 2019) - Daskalopoulou, Kyriaki; Gagliano, Antonina Lisa; Calabrese, Sergio; Li Vigni, Lorenza; Longo, Manfredi; Kyriakopoulos, Konstantinos; Pecoraino, Giovannella; D'Alessandro, Walter
Abstract : Forty-five gas samples have been collected from natural gas manifestations at the island of Kos—the majority of which are found underwater along the southern coast of the island. On land, two anomalous degassing areas have been recognized. These areas are mainly characterized by the lack of vegetation and after long dry periods by the presence of sulfate salt efflorescence. Carbon dioxide is the prevailing gas species (ranging from 88 to 99%), while minor amounts of N2 (up to 7.5%) and CH4 (up to 2.1%) are also present. Significant contents of H2 (up to 0.2%) and H2 S (up to 0.3%) are found in the on-land manifestations. Only one of the underwater manifestations is generally rich in N2 (up to 98.9%) with CH4 concentrations of up to 11.7% and occasionally extremely low CO2 amounts (down to 0.09%). Isotope composition of He ranges from 0.85 to 6.71R / R A, indicating a sometimes-strong mantle contribution; the highest values measured are found in the two highly degassing areas of Paradise beach and Volcania. C-isotope composition of CO2 ranges from -20.1 to 0.64‰ vs. V-PDB, with the majority of the values being concentrated at around -1‰ and therefore proposing a mixed mantle—limestone origin. Isotope composition of CH4 ranges from -21.5 to +2.8‰ vs. V-PDB for C and from -143 to +36‰ vs. V-SMOW for H, pointing to a geothermal origin with sometimes-evident secondary oxidation processes. The dataset presented in this work consists of sites that were repeatedly sampled in the last few years, with some of which being also sampled just before and immediately after the magnitude 6.6 earthquake that occurred on the 20 th of July 2017 about 15 km ENE of the island of Kos. Changes in the degassing areas along with significant variations in the geochemical parameters of the released gases were observed both before and after the seismic event; however, no coherent model explaining those changes was obtained. CO2 flux measurements showed values of up to about10 4   g × m − 2 × d − 1 in both the areas of Volcania and Kokkino Nero, 5 × 10 4   g × m − 2 × d − 1 at Paradise beach, and8 × 10 5   g × m − 2 × d − 1 at Therma spring. CO2 output estimations gave values of 24.6, 16.8, 12.7, and20.6   t × d − 1, respectively, for the above four areas. The total output of the island is74.7   t × d − 1 and is comparable to those of the other active volcanic/geothermal systems of Greece (Nisyros, Nea Kameni, Milos, Methana, and Sousaki).